O desafio da igreja para propor um mundo de paz - Lied, Leandro Luiz (2012)
The present research paper about The challenge of the church to propose a peaceful world consists in a study of the history of power relationships, within of development of Christianity formation and actions of Christians to overcome violence proposing, for this, the peace. The research hangs the history about chosen people by God and violence faced up, with the fights of empires and of their representatives, for control of nations and territories. The God s promise starts being fulfilled with the presence of Jesus Christ that proposes a peaceful world. After passing through a long and arduous apprenticeship, the process of Christianity construction proves the big mistakes committed which create more violence. Two thousand years proved that to build a peaceful world is necessary the distance of estate s power and building new relationships among society. Recent experiences, made by churches, show that this world, where all of us are just one, will be built from new alliances indicated by the Church, toward a Christian ecumenism, a solidarism and brotherhood actions. The practices developed by Christian churches in Brazil, in campaigns (Brotherhood Campaign) and in social pastorals indicate for this new way that moves away from institutionalized power and violence, allying directly with poor people, to build peace